Peran Persepsi,Kognisi Dan Emosi Terhadap Efektivitas Komunikasi Dan Negosiasi Pegawai Di Cafe Naya - Ariel Dohan; Fahri Ardiansyah; Muthia Firstry Mayhapdi; Ayunita Fitri; Susriyanti, Susriyanti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The effectiveness of communication and negotiation is not solely determined by logical reasoning and factual information, but is also strongly influenced by psychological factors. This article examines the influence of perception, cognition, and emotion on the effectiveness of communication and negotiation processes. Perception affects how messages and intentions are interpreted, cognition shapes information processing and decision-making, while emotion influences attitudes, behaviors, and negotiation strategies. Using a qualitative approach through literature review, this study analyzes how perceptual differences, cognitive biases, and emotional conditions impact mutual understanding and negotiation outcomes. The results indicate that positive perception, accurate cognitive processing, and effective emotional management significantly enhance communication effectiveness and increase the likelihood of successful negotiations. This study emphasizes the importance of psychological awareness in developing effective communication and negotiation strategies.